2001
DOI: 10.1067/mtc.2001.116950
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection by ischemic preconditioning and δ-opioid receptor activation in the isolated working rat heart

Abstract: Pharmacologic activation of delta-opioid receptors affords improvement of functional protection in isolated working rat hearts similar to that conferred by classic ischemic preconditioning. The combination of both pretreatments reduces ischemic cellular damage and further adds to postischemic functional recovery. These changes are reversed by naloxone, an observation providing evidence that ischemic preconditioning involves signaling through opioid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
17
0
3
Order By: Relevance
“…1,5,7,25 Many studies have demonstrated the effects of d receptor agonists to limit myocardial infarct size in models of cardiac ischemia and reperfusion. [5][6][7][8][9][10][11] However, most investigations involving these compounds have examined only their effects on specific receptors, tissues, or organs and have not looked at their impact on systemic processes and whole animal outcomes. 3 In this study, using an animal model of severe hemorrhagic shock, there was significant improvement in hemodynamic stability and a prolonged survival with DADLE treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,7,25 Many studies have demonstrated the effects of d receptor agonists to limit myocardial infarct size in models of cardiac ischemia and reperfusion. [5][6][7][8][9][10][11] However, most investigations involving these compounds have examined only their effects on specific receptors, tissues, or organs and have not looked at their impact on systemic processes and whole animal outcomes. 3 In this study, using an animal model of severe hemorrhagic shock, there was significant improvement in hemodynamic stability and a prolonged survival with DADLE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…DADLE (D-Ala2-Leu5-enkephalin) is one of the d receptor agonists that has been extensively studied with regard to its effect on myocardial function and has been used as a tool to investigate the mechanisms of IP. [9][10][11] It differs from other commonly studied opioid agonists in that it stimulates both d 1 and d 2 receptors and possibly has some k and m agonist activity. [12][13][14] There is also evidence that DADLE interacts with nonopioid-mediated cell processes and is antiapoptotic.…”
mentioning
confidence: 99%
“…Fortgesetzte Untersu chungen auf diesem Gebiet haben nun die Aufmerksamkeit auf endogene Opioi de gelenkt, denen offenbar tatsächlich ei ne umsatzdrosselnde Wirkung bei Win terschläfern und Nichtwinterschläfern zu kommt [33,55] und die in ersten Anwen dungsversuchen sogar einen organprotek tiven Effekt gezeigt haben [22].…”
Section: Schlüsselwörterunclassified
“…Miyokardiyal İÖ oluşumu sırasında etkin olan moleküller; reseptör bağımlı tetikleyiciler (adenozin, bradikinin, opioidler, siklooksijenaz ve lipoksijenaz ürünleri, norepinefrin, anjiotensin, endotelin), reseptör bağımsız tetikleyiciler (serbest radikaller, nitrik oksit, kalsiyum), İÖ medyatörleri (G proteinleri jenle aktive edilen protein kinazlar, ısı şok proteinleri, endotoksin, Janus Kinaz, sinyal transdüktörü ve transkripsiyon aktivatörü yolağı, Rho-Kinaz yolağı) ve İÖ uç efektörleri (adenozin trifosfata duyarlı potasyum kanalları [KATP]) olarak sınıflandırılırlar (9)(10)(11)(12)(13)(14)(15)(16) .…”
Section: Introductionunclassified